Screening for language delay after life-saving therapies in term-born infants. (28th December 2015) - Clark, Brenda G.; Acton, Bryan V.; Alton, Gwen Y.; Joffe, Ari R.; Dinu, Irina A.; Robertson, Charlene M. T.
Abstract: Background: Strong recommendations have been made for the periodic developmental surveillance, screening, and evaluation of children with CHD. This supports similar calls for all at-risk children in order to provide timely, structured early developmental intervention that may improve outcomes. The aim of this study was to determine the accuracy of screening for language delay after life-saving therapies using the parent-completed vocabulary screen of the language Development Survey, by comparing screening with the individually administered language scores of the Bayley Scales of Infant and Toddler Development, Third edition. Method: In total, 310 (92.5%) of 335 eligible term-born children, born between 2004 and 2011, receiving complex cardiac surgery, heart or liver transplantation, or extracorporeal membrane oxygenation in infancy, were assessed at 21.5 (2.8) months of age (lost, 25 (7.5%)), through developmental/rehabilitation centres at six sites as part of the Western Canadian Complex Pediatric Therapies Follow-up Group. Results: Vocabulary screening delay was defined as scores ⩽15th percentile. Language delay defined as scores >1 SD below the mean was calculated for language composite score, receptive and expressive communication scores of the Bayley-III. Delayed scores for the 310 children were as follows: vocabulary, 144 (46.5%); language composite, 125 (40.3%); receptive communication, 98 (31.6%); and expressive communication, 124 (40%). Sensitivity, specificity, positive predictive values, and negative predictive values of screened vocabulary delay for tested language composite delay were 79.2, 75.7, 68.8, and 84.3%, respectively. Conclusion: High rates of language delay after life-saving therapies are concerning. Although the screening test appears to over-identify language delay relative to the tested Bayley-III, it may be a useful screening tool for early language development leading to earlier referral for intervention.